Strategies for One-On-One Interaction to Enhance English Speaking Skills among EFL Students at MTS YMPI Rappang - Sherlan Argeta; Sam Hermansyah; Nur Hikmah; Isumarni (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This research aims to investigate the effectiveness of one-on-one interaction strategies in enhancing English speaking skills among EFL (English as a Foreign Language) students at MTs YMPI Rappang. The study identifies the challenges faced by students in speaking English, such as lack of confidence, limited speaking opportunities, and psychological barriers like anxiety. Using a qualitative approach, the research applies personalized interaction strategies in one-on-one sessions between teachers and students. Data were collected through observations, interviews, and documentation. Findings suggest that one-on-one interactions significantly improve students' speaking proficiency, boost their confidence, and reduce affective barriers. The study demonstrates that peer-based interactions and tailored feedback are crucial for fostering language fluency, accuracy, and spontaneous speech. This approach aligns with sociocultural theories of learning, particularly Vygotsky’s Zone of Proximal Development (ZPD) and Long’s Interaction Hypothesis. The research contributes to the development of practical strategies for teaching English in secondary schools, offering insights into effective pedagogical methods for enhancing communication skills among EFL learners.